Medical Mission Futures: German Protestant Missionaries and Modern Healthcare in Southern Highlands, Tanzania, 1891–1940. - Kaduma, Luoneko (Zamani: A Journal of African Historical Studies, 2024)
The history of colonial missionaries in Tanzania is marked by a complex interplay between evangelical efforts and the provision of Western biomedicine, which functioned as crucial mechanisms for conversion and cultural transformation. Missionaries viewed the improvement of African health as a project aimed at attracting converts and propagating Christianity. However, the available data indicates that, instead of genuinely expressing interest in converting to Christianity, the majority of Africans primarily sought mission medical assistance for medical reasons while maintaining strong connections to their traditional beliefs and healing practices. This paper, drawing from archival documents, ethnographic accounts, and missionary writings, focuses on Southern Highlands of Tanzania to explore how Protestant missionaries of the late nineteenth and early twentieth centuries sought to integrate healthcare and religious conversion in their missions. This endeavour, however, did not unfold as missionaries had anticipated. It sheds light on the overlooked aspect of the failed trajectory of medical missionaries, often absent from the broader narrative of colonial medical histories in Tanzania.